PENINGKATAN PEROLEHAN MINYAK EFEK RESIKEL RESIDU PENCAIRAN BATUBARA - Muhammad Hanif (Badan Pengkajian dan Penerapan Teknologi, 2007)
This paper presents the effect of recycle CLB (coal liquid bottom) on oil yieldfrom coal liquefaction process which contains of activated catalyst, organicresidue, and ash from coal. To recover activated catalyst from CLB is notextremely difficult but also very expensive. Therefore one possible way ofutilizing this activated catalyst and remaining convertible organic residue in CLBmore effectively is by recycling the CLB. As a result, the efficiency of coalliquefaction process can be improved significantly. Experiment using 1Lautoclave that's equipped with stirrer is conducted using Banko Coal at operatingtemperature of 450oC, initial hydrogen pressure of 12 MPa, and holding time 60min. Catalyst used in the experiment is medium grade limonite (MGL) fromSoroako with particle size less than 0.8 ïm and concentration of 3% mafc as Fe.Coal particle size is 200 mesh (74ïm).The experiment result suggests that CLBaddition can increase the oil yield of coal liquefaction. Recycle (additional) CLB of50 and 70wt% mafc can increase the oil yield from 25,71wt% mafc to 51,83 and65,7wt% mafc respectively.Kata kunci: hidrogenasi, likuifaksi, katalis, limonit, Soroako, pencairan batubara,CLB, daur ulang